Article Commentary: State-Specific Liquor Excise Taxes and Retail Prices in 8 US States, 2012. Issue 4 (October 2013) - Siegel, Michael; Grundman, Jody; DeJong, William; Naimi, Timothy S.; King, Charles; Albers, Alison B.; Williams, Rebecca S.; Jernigan, David H.
The authors investigated the relationship between state excise taxes and liquor prices in 8 states, using 2012 data for 45 brands. The authors made 6042 price observations among 177 liquor stores with online prices. Using a hierarchical model, the authors examined the relationship between excise taxes and product prices. State excise taxes were significantly related to liquor prices, with an estimated pass-through rate of 0.93. The proportion of price accounted for by excise taxes averaged 7.0%. The authors find that excise taxes do increase the price of alcohol, but states are not taking advantage of this opportunity to reduce alcohol-related morbidity and mortality.